Longitudinal transactional relationships between caregiver and child mental health during the COVID-19 global pandemic - Emily L. Robertson; Jennifer Piscitello; Ellyn Schmidt; Carolina Mallar; Bridget Davidson; Ruby Natale (BMC, 2021)
Abstract Background Emerging work examining the psychological impact of COVID-19 on children and families suggests that the relationship between pandemic-related stress, child psychosocial functioning, and caregiver mental health are interrelated. However, much of this research is unidirectional and thus little is known about the bidirectional cascading effects children and caregivers may experience. The current study examined the transactional relationships between caregiver and child mental health over time during the COVID-19 pandemic. Methods Linguistically, racially, and ethnically diverse caregivers (N = 286) of young children completed measures of caregiver mental health, caregiver pandemic-related stress, and child mental health (i.e., externalizing, internalizing, prosocial behavior) across three time points in the spring of 2020. Results Using autoregressive cross-lagged analyses, impaired caregiver mental health at Time 1 (April 2020) predicted increased caregiver pandemic-related stress at Time 2 (May 2020). Caregiver pandemic-related stress at Time 1 predicted increased child internalizing symptoms at Time 2 which, in turn, predicted increased caregiver pandemic-related stress at Time 3 (July 2020). Lastly, impaired caregiver mental health at Time 2 (May 2020) predicted increased child externalizing symptoms at Time 3 (July 2020). Conclusions Assessing transactional relationships between child and caregiver mental health during the COVID-19 pandemic is important to inform models of risk and resilience. Interventions at the level of the caregiver, the child, and/or the family should be considered as a way to interrupt potential negative developmental cascades.